1999
DOI: 10.1063/1.124142
|View full text |Cite
|
Sign up to set email alerts
|

Optical properties of β-Si3N4 single crystals grown from a Si melt in N2

Abstract: Large colored β-Si3N4 single crystals were successfully grown from a Si melt in N2. The transmission optical absorption of coloring β-Si3N4 single crystal shows that impurities introduce a midgap level of ∼2.4 eV into the wide band gap of ∼5.3 eV in nondoped Si3N4. The infrared transmission spectrum and electron probe x-ray microanalysis of β-Si3N4 samples show that the solution of the Al element affects the silicon–nitrogen molecular vibration and the states within the band gap of β-Si3N4. The obtained result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
61
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(66 citation statements)
references
References 5 publications
4
61
1
Order By: Relevance
“…15,16 We have reported, for the first time, ferromagnetism above room temperature ͑RT͒ in Mn/ Si 3 N 4 multilayered films. 17 The structural and electronic properties of few samples were studied by x-ray absorption spectroscopy ͑XAS͒ and x-ray magnetic circular dichroism, indicating the presence of a distorted noncentrosymmetric Mn 3 N 2 phase with slightly shorter Mn-N distances, which was proposed to be the origin of the ferromagnetism in this system.…”
Section: Introductionmentioning
confidence: 87%
“…15,16 We have reported, for the first time, ferromagnetism above room temperature ͑RT͒ in Mn/ Si 3 N 4 multilayered films. 17 The structural and electronic properties of few samples were studied by x-ray absorption spectroscopy ͑XAS͒ and x-ray magnetic circular dichroism, indicating the presence of a distorted noncentrosymmetric Mn 3 N 2 phase with slightly shorter Mn-N distances, which was proposed to be the origin of the ferromagnetism in this system.…”
Section: Introductionmentioning
confidence: 87%
“…The material is also a wide-band gap semiconductor with a band gap of 5.3 eV, in which the mid-gap levels can be introduced by doping for tailoring its electronic/optical properties [10,11]. To date, one-dimensional Si 3 N 4 nanostructures have been synthesized via different methods [12].…”
Section: Introductionmentioning
confidence: 99%
“…Similar to III-N compounds such as GaN and AIN, Si 3 N 4 is also an excellent host material in terms of high dopant concentration, mechanical and thermal properties and chemical stabilities. It has been demonstrated that by introducing midgap levels into the wide band gap of 5.3 eV in nondoped Si 3 N 4 , the emission of green to ultraviolet light can be achieved [3][4][5][6]. The synthesis of Si 3 N 4 nanomaterials is of particular interest since they could be promising candidates for fabricating nanocomposites and electronic/optic nanodevices that can be operated at extreme conditions such as high temperatures, corrosive environments, high power and radiation environments.…”
Section: Introductionmentioning
confidence: 99%